2015
DOI: 10.1515/pjvs-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high hydrostatic pressure on Campylobacter jejuni in poultry meat

Abstract: Campylobacter jejuni inactivation by high pressure processing (HPP) in poultry meat (chicken breast) was investigated. The pressure was created by high hydrostatic pressure piston-cylinder food processor. Contaminated with C. jejuni (10 8 CFU g -1 ) samples of ground poultry meat were hermetically sealed in a polyamide-polyethylene bags and exposed to HPP for 9 different combinations of pressure (200 MPa, 300 MPa and 400 MPa) and time (5 min, 10 min and 15 min). Quantitative bacteriological analysis was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…), thus injured cells become sensitive and might not have the ability to resuscitate and grow on selective media within incubation times. However, in recent studies, selective media were still used for enumeration of other bacteria after HHP treatment in food, that is, Listeria monocytogenes , Campylobacter jejuni or Salmonella enterica (Jackowska‐Tracz and Tracz ; Bover‐Cid et al . ; Rubio et al .…”
Section: Resultsmentioning
confidence: 99%
“…), thus injured cells become sensitive and might not have the ability to resuscitate and grow on selective media within incubation times. However, in recent studies, selective media were still used for enumeration of other bacteria after HHP treatment in food, that is, Listeria monocytogenes , Campylobacter jejuni or Salmonella enterica (Jackowska‐Tracz and Tracz ; Bover‐Cid et al . ; Rubio et al .…”
Section: Resultsmentioning
confidence: 99%
“…In this same study, the researchers demonstrated that organic acid washes reduced Campylobacter contamination on chicken liver. High-pressure processing has been shown to reduce pathogens in other chicken products (Solomon and Hoover, 2004 ; Jackowska-Tracz and Tracz, 2015 ) and it may also be effective in chicken liver.…”
Section: Discussionmentioning
confidence: 99%
“…Further details about commercialized meat product of HPP are detailed elsewhere (78). (79). According to the pressure applied, the temperature varies from 0 to 10 • C. When the lowest pressure (200 MPa) was applied, C. jejuni exposed resistance and no significant reduction was achieved regardless of the duration of HPP treatment.…”
Section: High-pressure Processingmentioning
confidence: 99%
“…According to the pressure applied, the temperature varies from 0 to 10 • C. When the lowest pressure (200 MPa) was applied, C. jejuni exposed resistance and no significant reduction was achieved regardless of the duration of HPP treatment. Gram-negative bacteria are generally more susceptible to pressure compared to Gram-positive bacteria (79). Sheen et al (2015) reported also that the inactivation of Salmonella spp.…”
Section: High-pressure Processingmentioning
confidence: 99%
See 1 more Smart Citation